Potential influence of red beetroot juice consumption on endothelial function - Fischer, Emily, author; Litwin, Nicole, author; Hartley, Shannon, author; Van Ark, Hannah, author; Weir, Tiffany L., author; Melby, Christopher L., author; Johnson, Sarah A., author (Colorado State University. Libraries, 2017)
Atherosclerotic cardiovascular disease (CVD) is the leading cause of death worldwide. Endothelial dysfunction is a major initiating step in the pathophysiology of CVD. Red beetroot juice (RBJ) contains bioactive compounds including phenolic acids, flavonoids, betalains, ascorbic acid, and nitrate. Previous research suggests RBJ it can improve endothelial function. In a randomized, double-blind, placebo-controlled crossover clinical trial, 16 healthy, overweight/obese men and postmenopausal women aged 40-65 years are consuming RBJ, nitrate-free RBJ, placebo + nitrate, or placebo for 4 weeks. Endothelial function is assessed at baseline and 4 weeks. RBJ is anticipated to exert the greatest effects on endothelial function.
102 - Emily Kay Fischer
Keywords: endothelial cell; cardiovascular disease; red beetroot juice; oral bacteria; dietary nitrate